Clinico-epidemiological profile of disorders of sex development at a tertiary referral hospital in South Kalimantan, Indonesia - Maria Ulfah; Indra Widjaya Himawan; Niarsari Anugrahing Putri; Naisya Balela; Aulia Mufida; Nashwa Rifda Agustina; Nur Aisyah Munawaroh Ayu (Faculty of Medicine, Universitas Trisakti, 2026)
BackgroundDisorders of sex development (DSD) comprise a group of complex conditions that pose significant diagnostic and clinical issues. This study aimed to describe the clinical spectrum, temporal patterns, and geographical distribution of DSD cases at a tertiary referral hospital in South Kalimantan, Indonesia. MethodsThis retrospective descriptive study analyzed medical records of patients with clinical features suggestive of DSD at Ulin General Hospital, Banjarmasin, between 2022 and 2025. Clinical diagnoses were established by a consultant pediatric endocrinologist based on phenotypic evaluation, consistent with approaches used in other Indonesian centers with limited access to karyotyping. Variables assessed included clinical diagnosis, age, sex, year of diagnosis, and domicile, whilst spatial analysis used Geographic Information System (GIS) software. ResultsAmong the 100 cases analyzed, severe hypospadias dominated (45 cases, 45%), followed by primary amenorrhea (28 cases, 28%) and micropenis (13 cases, 13%). Males accounted for 67% of cases, females for 32%, and one case had undetermined sex. Mean age at diagnosis was 9.41 ± 7.32 years (range: neonatal period to 35.4 years). Geographic analysis revealed notable disparities, with Banjarmasin contributing 40% of cases, while other districts each accounted for approximately 5%. ConclusionsThe findings indicate delayed diagnosis, potential underdiagnosis in rural areas, and geographic disparities that likely reflect differences in access to tertiary services rather than true occurrence variation. This highlights the importance of evaluating boys presenting with proximal penile hypospadias or micropenis and girls with primary amenorrhea for timely intervention. Strengthening early detection and expanding diagnostic capacity are essential to improve DSD clinical outcomes.